Taiwan's COVID-19 experience
1 online resource.
Keywords: "This book explores and develops the ongoing conversation about how Taiwan navigated through the COVID-19 pandemic. Emphasizing the themes of governance and governmentality, it moves the foci of the discussion from COVID policies to the social and political orders undergirding the statecraft of pandemic management. Furthermore, it analyses how the pandemic fostered a historical moment at which new forms of governance and governmentality were beginning to take root. It also situates Taiwan's precarious nationhood in its global context, thereby challenging a prevalent methodological nationalism - the assumption that the nation is a natural unit of analysis whose borders are more or less unquestioned - and contributing to decolonizing Western theories with perspectives from the Global South. Presenting rich original materials on the legal and public debates, individual reflections, and grassroots campaigns during COVID, this book will be essential reading for students and scholars of Taiwan's governance and social health policy, as well as medical anthropology and sociology"--